The Correlation between Lifestyle and the Severity of Diabetic Peripheral Neuropathy - Ritonga, Sukhri Herianto; Harahap, Choirunnisa; Hidayah, Arinil (Universitas Prima Indonesia, 2024)
Diabetic peripheral neuropathy (DPN) is a significant complication of diabetes mellitus (DM), whose incidence is consistently increasing from year to year. Lifestyle is a considerable risk factor for increasing DM complications. To prevent the occurrence of DPN, it is necessary to carry out a more in-depth analysis of the correlation between lifestyle and DPN. The purpose of this study was to determine the correlation between lifestyle and the severity of diabetic peripheral neuropathy. The research design was a case-control study. The sampling technique used was sequential sampling. Respondents in this study were 94 people divided into two groups: 47 as the case group and 47 as the control group. Based on the Chi-Square test of the relationship between lifestyle and the severity of diabetic peripheral neuropathy, p-value = 0.000 < (0.05) OR=10.084; 95% CI=3.712-27.395). It could be concluded that there was a correlation between lifestyle and the severity of diabetic peripheral neuropathy. This research could be a learning material and additional knowledge for respondents regarding the importance of improving a healthy lifestyle in every nursing intervention to prevent an increase in the number of degenerative diseases, especially DM, and reduce the incidence of diabetic peripheral neuropathy.